Correlational Study: Teacher Perceptions and The Implementation of Education for Sustainable Development Competency for Junior High School Teachers - Dadi Mulyadi; Mohammad Ali; Eero Ropo; Laksmi Dewi (Journal of Education Technology, 2023)
ESD competence is key for teachers to implement ESD in schools so that education can make a real contribution to achieving sustainable development goals. This study analyzes the relationship between perceptions of teacher ESD competence and ESD implementation in Junior High Schools (JHS). This study uses a correlational study. The population in this study included JHS teachers. The research sample consisted of 384 teachers who were taken using a multistage sampling technique by taking teachers from 3 sub-districts in 6 urban districts. The data collection method used is by distributing questionnaires to respondents. Data analysis is using percentage analysis technique amd Pearson correlation analysis technique. The results of this study indicate that teachers need ESD competencies because teachers feel that the implementation of ESD in schools is still in the average category. So teachers hope to acquire competencies related to ESD in more depth. Based on this, it is hoped that policymakers at the national level, local governments, and even the schools themselves will organize activities to improve ESD competence for teachers in various forms of training, seminars, and others. This is done so that the implementation of ESD in schools can be maximized so that teachers, as the spearhead of education, can make a real contribution to achieving the 2030 agenda.